Anti-inflammatory and anti-aging activity of hydrogel with active ingredient Phyllantus emblica L. fruit nanosimplicia - Masfria Masfria; Sumaiyah Sumaiyah; Hafid Syahputra; Jennifer Jenifer (Institue of Medicinal Plants, ACECR, 2023)
Background: Phyllantus emblica contains quite high levels of vitamin C as an antioxidant, premature aging and anti-inflammatory. Simplicia is formulated into a hydrogel because it has good dispersion power on the skin. Objective: This research aims to develop a hydrogel formula with the active ingredient Phyllantus emblica L. Fruit nanosimplicia as an anti-inflammatory and anti-aging. Methods: Nano simplicia is made using a high-energy ball mill and characterized through phytochemical analysis, particle size analysis, Fourier transform infrared spectroscopy, and scanning electron microscopy. Hydrogels are formulated with simplicia concentrations (2, 4, 6 %). Assessment of hydrogels encompasses organoleptic evaluations, consistency, dispersibility, pH, thickness, stability, skin irritation, efficacy against aging, and anti-inflammatory. Results: The anti-aging hydrogel made from P. emblica fruit nanosimplicia is a dark brown, uniform substance with a pH range of 5.26-6.28 and spreadability between 6.1-6.8. It remains stable after 4 weeks of storage at room temperature and is non-irritating to the skin. Results showed that the 6 % hydrogel preparation was the most effective in increasing moisture by 17.90 %, improving evenness by 15.83 %, reducing pore size by 15.30 %, diminishing pore spots by 22.67 %, and decreasing wrinkles by 28.06 %. Hydrogel concentrations of 2 %, 4 %, and 6 % showed inhibitory results of 0.7 %, 6.6 %, and 8.19 % respectively. Conclusion: Phyllanthus emblica nanosimplicia was successfully incorporated into a hydrogel formulation and remained stable for four weeks of storage. Hydrogel 6% exhibited superior anti-aging and anti-inflammatory properties.